Measurement of the Z(-> l(+)l(-))gamma production cross-section in pp collisions at root s=13 TeV with the ATLAS detector - Çetin, Serkant Ali (Springer, 2020)
The production of a prompt photon in association with a Z boson is studied in proton-proton collisions at a centre-of-mass energy s = 13 TeV. The analysis uses a data sample with an integrated luminosity of 139 fb(-1) collected by the ATLAS detector at the LHC from 2015 to 2018. The production cross-section for the process pp -> l(+)l(-)gamma + X (l = e, mu) is measured within a fiducial phase-space region defined by kinematic requirements on the photon and the leptons, and by isolation requirements on the photon. An experimental precision of 2.9% is achieved for the fiducial cross-section. Differential cross-sections are measured as a function of each of six kinematic variables characterising the l(+)l(-)gamma system. The data are compared with theoretical predictions based on next-to-leading-order and next-to-next-to-leading-order perturbative QCD calculations. The impact of next-to-leading-order electroweak corrections is also considered.
Keywords: Hadron-Hadron scattering (experiments)